Cortactin Is Involved in the Entry of Coxiella burnetii into Non-Phagocytic Cells - Rosales, Eliana M.; Aguilera, Milton O.; Salinas, Romina P.; Carminati, Sergio A.; Colombo, María I.; Martinez-Quiles, Narcisa; Berón, Walter (PLOS ONE, 2012)
Background Cortactin is a key regulator of the actin cytoskeleton and is involved in pathogen-host cell interactions. Numerous pathogens exploit the phagocytic process and actin cytoskeleton to infect host cells. Coxiella burnetii, the etiologic agent of Q fever, is internalized by host cells through a molecular mechanism that is poorly understood. Methodology/Principal Finding Here we analyzed the role of different cortactin motifs in the internalization of C. burnetii by non-phagocytic cells. C. burnetii internalization into HeLa cells was significantly reduced when the cells expressed GFP-cortactin W525K, which carries a mutation in the SH3 domain that renders the protein unable to bind targets such as N-WASP. However, internalization was unaffected when the cells expressed the W22A mutant, which has a mutation in the N-terminal acidic region that destroys the protein’s ability to bind and activate Arp2/3. We also determined whether the phosphorylation status of cortactin is important for internalization. Expression of GFP-cortactin 3F, which lacks phosphorylatable tyrosines, significantly increased internalization of C. burnetii, while expression of GFP-cortactin 3D, a phosphotyrosine mimic, did not affect it. In contrast, expression of GFP-cortactin 2A, which lacks phosphorylatable serines, inhibited C. burnetii internalization, while expression of GFP-cortactin SD, a phosphoserine mimic, did not affect it. Interestingly, inhibitors of Src kinase and the MEK-ERK kinase pathway blocked internalization. In fact, both kinases reached maximal activity at 15 min of C. burnetii infection, after which activity decreased to basal levels. Despite the decrease in kinase activity, cortactin phosphorylation at Tyr421 reached a peak at 1 h of infection. Conclusions/Significance Our results suggest that the SH3 domain of cortactin is implicated in C. burnetii entry into HeLa cells. Furthermore, cortactin phosphorylation at serine and dephosphorylation at tyrosine favor C. burnetii internalization. We present evidence that ERK and Src kinases play a role early in infection by this pathogen.